2018
DOI: 10.1155/2018/1347513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot-Water Blanching Pretreatment on Drying Characteristics and Product Qualities for the Novel Integrated Freeze-Drying of Apple Slices

Abstract: The effect of hot-water blanching (HWB) on drying characteristics and product qualities of dried apple slices with the novel integrated freeze-drying (NIFD) process was investigated by comparing with 3 different FD methods. Compared with the NIFD process without HWB pretreatment (VF-FD), the NIFD process with HWB pretreatment (HWB-VF-FD) resulted in a significantly higher mass loss and more sufficient freezing in vacuum-frozen samples, significantly higher rehydration ratio (RR), higher shrinkage ratio (SR), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 36 publications
7
46
0
4
Order By: Relevance
“…The lowering of the fiber content by the treatment would be the consequence of a destruction of these compounds by heat treatment and elimination in the blanching water. Similar observations have also been reported by Wang et al [24], who observed a loss of watersoluble compounds such as fibres following blanching. The interactive effect would be due to the fact that the different varieties of Irish potato studied are very rich in soluble fiber, which would therefore be easily extracted and eliminated by blanching water.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lowering of the fiber content by the treatment would be the consequence of a destruction of these compounds by heat treatment and elimination in the blanching water. Similar observations have also been reported by Wang et al [24], who observed a loss of watersoluble compounds such as fibres following blanching. The interactive effect would be due to the fact that the different varieties of Irish potato studied are very rich in soluble fiber, which would therefore be easily extracted and eliminated by blanching water.…”
Section: Discussionsupporting
confidence: 90%
“…This change leads to an increase in membrane permeability and thus increased water removal through evaporation [23]. Wang et al [24], also demonstrated that water blanching reduces the water content of apples. It should be noted that the water levels obtained (<14%) are favourable for good conservation in tropical areas over a long period of time [25].…”
Section: Discussionmentioning
confidence: 98%
“…The ascorbic acid content in the OD and ST samples was signifi cantly higher than in the non-pretreated sample and the opposite tendency was observed in the SB, SB+OD, and UT samples. The loss in V C was attributed to the thermal disruption and leakage of water-soluble V C during pretreatment [Wang et al, 2018;Horuz et al, 2017]. However, it was reported that the presence of sugar would stabilize vitamin C in fruits [Pasławska et al, 2017].…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…Pretreatments prior to drying are often used to reduce the initial moisture content, accelerate the drying process, improve quality of dried products, modify the physicochemical properties of dried material, and infl uence the heat and mass transfer during drying [Doymaz et al, 2010]. Some common pretreatments include blanching, osmotic dehydration, sulfi te treatment or a combination of the above treatments [Camel et al, 2019;Wang et al, 2018;Doymaz et al, 2010]. The sulfi ting at low concentration is the most commonly used pretreatment method for apples and other fruits for its features of simple operation and well preserved color of products.…”
Section: Introductionmentioning
confidence: 99%
“…Its principle is to freeze the solvent contained inside the products to a solid state and then induce sublimation of the frozen material as vapor under vacuum conditions to achieve the goal of drying (Antal, Tarek‐Tilistyák, Cziáky, & Sinka, ; Gao et al., ). It can better preserve most of the initial material properties, such as taste, aroma, color, flavor, nutrients, biological activity, and rehydration ability (Georgiev, Kosturski, Margenov, & Stary, ; Wang, Fu, Chen, Hu, & Xie, ). Furthermore, it also retains its original shape, appearance, and texture with minimal shrinkage and high porosity (Ma et al., ; Ma, Qu, & Sun, ).…”
Section: Introductionmentioning
confidence: 99%